Etiological evaluation of convulsions in children between 1 month to 5 years of age - Mamillapalli, Bharathi; A., Penchalaiah (International Journal of Contemporary Pediatrics, 2017)
Background: Convulsions are the most common pediatric neurological disorder worldwide. The incidence is highest in children younger than 3 years of age with a decreasing frequency in older children. The different causes of seizures are febrile convulsions, CNS infections, neurologic or developmental, metabolic, traumatic or vascular, idiopathic or epilepsy, oncologic. The objective of our study is to find out the various etiologies of convulsions in children between 1 month to 5 years of age. Methods: 200 consecutive cases admitted to the hospital with convulsions in this particular age group were studied by detailed history, thorough examination and stepwise investigations including blood counts, CSF analysis, EEG and neuroimaging studies. Results: The most common cause for seizures in our study was febrile seizures (34.5%). Hypocalcemic seizures were the predominant cause (13%) between 1 month to 1 year of age. Other causes included viral encephalitis (20%), pyogenic meningitis (11%), TB meningitis (8.5%), epilepsy (8%), hypoglycemia (2%), neurocysticercosis (1%), head injury (1%) late HDN (0.5%). Cerebral palsy, mental retardation syndromes with developmental delay and epilepsy constituted 5.5% of the cases. Conclusions: Convulsions in children can be due to various underlying pathology. A detailed history, thorough examination and certain investigations helps to recognize the cause for the convulsions and can be treated accordingly.